The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1985
DOI: 10.1207/s15328023top1203_16
|View full text |Cite
|
Sign up to set email alerts
|

Teaching the Relevance of Statistics through Consumer-Oriented Research

Abstract: Students in a small experimental design class obtained information about statistical and research applications concerning a variety of products advertised by different companies. The resulting data were perceived to have several advantages for the students: (a) it made collecting and interpreting data more interesting and less mysterious, (b) it helped them to understand how research design and statistics are used in real-life situations, and (c) it helped them to make more discerning judgments about advertise… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
0
3

Year Published

1993
1993
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(24 citation statements)
references
References 5 publications
0
21
0
3
Order By: Relevance
“…Other studies [9,10,18,19,20,21] showed a relationship between the ATS and academic outcomes or the professional use of statistics. They have confirmed the existence of a definite correlation between students' attitudes and their performance in this area.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Other studies [9,10,18,19,20,21] showed a relationship between the ATS and academic outcomes or the professional use of statistics. They have confirmed the existence of a definite correlation between students' attitudes and their performance in this area.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Las actitudes influyen en el proceso de enseñanza-aprendizaje y a su vez, la educación tiene un amplio poder sobre ellas. Así, se aprende mejor aquello que produce mayor agrado, y una educación adecuada puede mejorar las actitudes de los estudiantes ante una materia determinada En este sentido hay estudios que avalan la relación entre el logro y la actitud del alumnado hacia las Matemáticas (Morris et al, 1978;Hendel, 1980;Wigfield y Meece, 1988); e igualmente los estudios demuestran el valor predictivo de las actitudes en el logro de la Estadística (Guàrdia et al, 2006;Bayot et al, 2005;Elmore y Vasu, 1986;Beins, 1985).…”
Section: Fundamentación Teóricaunclassified
“…La actitud es un buen predictor de la asimilación de contenidos, del futuro uso de los mismos, de la motivación para el aprendizaje y del rendimiento (Beins, 1985). La actitud negativa bloquea el uso de ésta en el futuro profesional del alumno.…”
Section: Introductionunclassified
“…Roberts y Saxe (1982); Beins (1985); Wise (1985); Katz y Tomezik (1988); Vanhoof et al (2006); Evans (2007) showed the relationship between attitude toward statistic and academic outcomes or the professional use of this tool. They have confirmed the existence of positive correlation between students' attitudes and their performance in this area.…”
Section: Literature Reviewmentioning
confidence: 99%